Antinociceptive and antiarthritic activity of Cissampelos pareira roots - Amresh G.; Singh P.N.; Rao Ch.V. (My University, 2025)
In the present study, 50% aqueous ethanolic extract of Cissampelos pareira (Menispermaceae) roots (C. pareira) at the dose levels of 100-400 mg/kg, once daily for 3 days exhibited significant (P < 0.001) resistance against mechanical pain after 30 min in analgesymeter induced pain in mice. In acetic acid (0.6%; i.p.) inducing writhing, Cissampelos pareira significantly (P < 0.05) decreased the writhing episodes; the degree of percent protection at 200 and 400 mg/kg was 22.73 and 51.63. The hot plate reaction time was increased by 2.07 (P < 0.05) and 2.70 (P < 0.001) folds. respectively. Further Cissampelos pareira showed the dose dependent significant protective effect against complete Freund's adjuvant induced arthritis. The percentage protection on the 18th day was 40.54 (P < 0.01) and 71.52 (P < 0.001) at 200 and 400 mg/kg respectively. Lysosomal enzymes (acid phosphatase and N-acetyl glucosaminidase) were decreased by 50% (P < 0.01) and 26.26% (P < 0.05) by using Cissampelos pareira, dextramethasone decreased them 56.56% (P < 0.01) and 31.82% (P < 0.01) and the glycoprotein contents (total hexose and sialic acid) were increased by 1.55-folds (P < 0.01) and 1.51-folds (P < 0.05) by using Cissampelos pareira while dextramethasone increases them by 1.51-folds (P < 0.001) and 1.60-folds (P < 0.01) respectively in stomach homogenate with respect to arthritic group. The increased pain threshold and protective effect against CFE by Cissampelos pareira vindicated its medicinal value in treatment of pain and arthritis. © 2007 Elsevier Ireland Ltd. All rights reserved.